Radiation knowledge and anxiety levels among residents proximity to the world’s first AP1000 nuclear power unit - Jiadi Guo; Zhiqiang Xuan; Cuiping Lei; Taotao Zheng; Zhongjun Lai; Xiaoji Hao; Shunfei Yu; Yiyao Cao (Frontiers in Public Health)
ObjectiveAssess the level of radiation-related knowledge (RRK) and nuclear energy-related knowledge (NERK) among residents near the Sanmen Nuclear Power Plant, the first project adopted the Advanced Passive Pressurized Water Reactor (AP1000) technology.MethodsIn this study, respondents were selected using stratified multi-stage random sampling for residents aged 18 years and above living within 30 kilometers of the Sanmen Nuclear Power Station. Respondents were surveyed face-to-face by investigators who received standardized training. The results of the survey were collated and analysed to assess the RRK and NERK levels of the respondents from both subjective and objective perspectives, and the anxiety levels were assessed using the Likert Scale. Factors affecting RRK, NERK and anxiety levels of residents were analysed using multiple linear regression analysis.ResultsThe study interviewed 751 individuals. Participants correctly answered an average of 2.76 out of 7 objective radiation knowledge questions, yielding a 39.4% RRK cognition rate. For nuclear energy knowledge, the average was 2.14 out of 7, resulting in a 30.5% NERK cognition rate. Spearman’s correlation and multiple linear regression analyses revealed that higher education and younger age were positively correlated with RRK and NERK. Gender significantly influenced NERK, with males scoring higher than females. Anxiety levels were inversely related to age and directly related to education. Regression analyses also indicated that occupation affected nuclear-related anxiety, and married and unmarried individuals exhibited higher anxiety levels than widowed individuals.ConclusionResidents near the Sanmen Nuclear Power Station showed improvements in RRK and NERK, but levels remained low. Both RRK and NERK correlated with age and education, while NERK was also linked to gender. Anxiety among residents was associated with age, education, occupation, and marital status. These findings highlight the need for improved public education on RRK and NERK, effective engagement strategies, and measures to address residents’ anxiety to enhance decision-making and social trust regarding nuclear safety.